The Cost of Reproduction in a Cooperatively Breeding Mammal: Consequences of Seasonal Variation in Rainfall, Reproduction, and Reproductive Suppression - Jacobs, Paul Juan; Hart, Daniel William; Suess, Tobias; Janse van Vuuren, Andries Koch; Bennett, Nigel Charles (Frontiers in Physiology, 2021)
Biological investments, such as reproduction, are influenced by both biotic and abiotic factors and their interactions. The trade-off between reproduction and survival has been well established. Seasonally breeding species, therefore, may exhibit variations in these trade-offs, but there is a dearth of knowledge concerning this. This study investigated the physiological cost of reproduction (measured through oxidative stress) across seasons in the cooperatively breeding highveld mole-rat (Cryptomys hottentotus pretoriae), one of the few seasonal breeding mole-rats. Oxidative stress indicates elevated reactive oxygen species levels, which can overwhelm antioxidant defences resulting in damaged proteins, lipids and DNA, which overall can reduce longevity and compromise reproduction. Oxidative markers such as total oxidant status (TOS-measure of total peroxides present), total antioxidant capacity (TAC), OSI (oxidative stress index) and malondialdehyde (MDA) are utilised to measure oxidative stress. In this study, breeding and non-breeding male and female mole-rats were captured during the dry season (breeding period) and wet season (non-breeding period). There was an apparent cost of reproduction in the highveld mole-rat; however, the seasonality pattern to the cost of reproduction varied between the sexes. Breeding females had significantly higher MDA during the breeding period/dry season in comparison to the non-breeding period/wet season; this is possibly a consequence of bearing and nursing offspring. Contrastingly, breeding males showed increased oxidative damage in the non-breeding/wet season compared to the breeding/dry season, possibly due to increased activities of protecting their mating rights for the next breeding/dry season, but this was not significant. Interestingly, during the non-breeding period/wet season, non-breeding females are released from their reproductive suppression, which resulted in increases in TOS and OSI, which again indicated that just the mere ability to be able to breed results in a cost (oxidative stress). Therefore we can speculate that highveld mole-rats exhibited seasonal variation in redox balance brought about by variation in abiotic variables (e.g. rainfall), physiology and behaviour. We conclude that physiological changes associated with reproduction are sufficient to induce significant acute oxidative stress in the plasma of female highveld mole-rats, which become alleviated following transition to the non-breeding season/wet period suggesting a possible hormetic effect.